Precision medicine in pediatric oncology: Lessons learned and next steps. Issue 3 (17th October 2016) - Mody, Rajen J.; Prensner, John R.; Everett, Jessica; Parsons, D. Williams; Chinnaiyan, Arul M.
Abstract: The maturation of genomic technologies has enabled new discoveries in disease pathogenesis as well as new approaches to patient care. In pediatric oncology, patients may now receive individualized genomic analysis to identify molecular aberrations of relevance for diagnosis and/or treatment. In this context, several recent clinical studies have begun to explore the feasibility and utility of genomics‐driven precision medicine. Here, we review the major developments in this field, discuss current limitations, and explore aspects of the clinical implementation of precision medicine, which lack consensus. Lastly, we discuss ongoing scientific efforts in this arena, which may yield future clinical applications.